PREVALENCE, MANAGEMENT AND OUTCOME OF GASTROSCHISIS : A COMPREHENSIVE SYSTEMATIC REVIEW - Utama Putri, Diana; Ponco Wibowo, Yulian (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Gastroschisis (GS) is a congenital abdominal defect that is usually located on the right side of the umbilical cord, characterized by the discharge of the intraperitoneal tube and other abdominal contents into the amniotic cavity, and ultrasonography reveals that the foetal bowel floats in the amniotic fluid. GS develops in the early embryonic period, and the cause of most gastroschisis cases is unknown. The aim: The aim of this study to show about prevalence, management and outcome of gastroschisis. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 7 articles, whereas the results of our search on SagePub get 128 articles, on Google Scholar 685 articles. Records remove before screening are 820, so we get 352 articles fos screening. After we screened based on record exclude, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Basic management of neonates with gastroschisis entail wrapping the herniated viscera, either with a plastic/cling wrap or a homemade silo from a saline intravenous bag in institutions where preformed silo bags are not freely available. If the neonate is haemodynamically stable, not in respiratory distress and presents early to the facility, the reduction of herniated viscera and primary fascial closure would be attempted.